Analysis of Non-Performing Loans and Interest Rates on Bank Jasa Jakarta's Profitability (2004–2024) - Alexandra Natasha Salwa; Agus Maolana Hidayat (Entrepreneurship Faculty, Universitas Garut, 2026)
This study examines the effect of Non-Performing Loan Gross (NPL Gross), Net Interest Margin (NIM), and BI Rate on the profitability of PT Bank Jasa Jakarta, measured by Return on Equity (ROE), over the period 2004–2024. Secondary data from 21 annual observations were analyzed using Ordinary Least Squares (OLS) multiple linear regression via EViews 13, with ROE(−1) included as a control variable, classical assumption tests confirmed normality, no multicollinearity (VIF < 2), no autocorrelation (DW = 1.886), and homoscedasticity. NPL Gross did not significantly affect ROE (p = 0.081) due to its consistently narrow variation. NIM negatively and significantly affected ROE (p = 0.014; coeff. = −17.97), reflecting an efficiency–profitability paradox during digital transformation. BI Rate negatively and significantly affected ROE (p = 0.001; coeff. = −7.85), consistent with monetary transmission theory. Simultaneously, the four variables explained 98.77% of ROE variation (Adjusted R² = 0.9877). Margin expansion during capital-intensive digital transformation does not improve profitability without operational cost discipline, management is advised to prioritize BOPO reduction and diversify funding toward low-cost CASA to reduce monetary policy sensitivity.